2021
DOI: 10.14256/jce.2889.2020
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of RC columns under cyclic uniaxial and biaxial lateral load

Abstract: A numerical finite element study is conducted in this paper to examine structural behaviour of high strength RC columns exposed to biaxial and uniaxial lateral displacement histories with constant axial load. The numerical analysis of 24 models was made using ABAQUS / CAE. The comparison between numerical analysis and experimental results shows good agreement through validations. The considered parametric study involves determination of the longitudinal reinforcement ratio, total cross-sectional area of confin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Given that the samples differ by less than 10%. This finding is consistent with Harba and Abdulridha [50] and Risan et al [51].…”
Section: Conclusion and Results -Certification Resultssupporting
confidence: 92%
“…Given that the samples differ by less than 10%. This finding is consistent with Harba and Abdulridha [50] and Risan et al [51].…”
Section: Conclusion and Results -Certification Resultssupporting
confidence: 92%
“…Tensile compression stress on beam supports has gone down since CFRP was used. Several studies [13][14][15][16][17][18][19] have shown that CFRP may improve how well it absorbs energy, holds loads, and bends in the middle. The study showed that rebar-reinforced plastic sheets made lightweight concrete slabs more resistant to bending.…”
Section: Introductionmentioning
confidence: 99%
“…Most buildings worldwide are constructed using reinforced concrete. The major causes of the damages in the existing reinforced concrete structures are design deficiencies, strength inadequacy, natural calamities, errors in construction, durability, accidental loads, etc [1][2][3][4][5][6]. Different strengthening methods are available to minimise the effect of damages and extend the life of structures.…”
Section: Introductionmentioning
confidence: 99%